Effects of Intermittent Fasting on Weight Loss and Metabolic Health - Anna Kaźmierczak; Klaudia Perkowska; Anna Kiełb; Agata Borkowska; Wiktoria Izdebska; Jakub Stanek; Patrycja Sornek; Igor Pawlak; Anna Mich; Radosław Ciesielski (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Purpose: Intermittent fasting (IF) has become a popular strategy for combating obesity and improving metabolic health. This dietary regimen alternates between periods of fasting and eating, aiming to enhance cellular health and increase longevity. With obesity rates doubling globally since 1990 and metabolic diseases on the rise, IF offers a potential solution by promoting metabolic benefits and reducing obesity-related conditions. Material and Method: This review examines various IF methods, including alternate-day fasting, the 5:2 diet, and time-restricted eating. The analysis focuses on the impact of these fasting methods on body weight, insulin sensitivity, and lipid profiles, based on a compilation of studies that explore the physiological effects and health outcomes associated with IF. Results: IF has shown to be effective in reducing body weight and improving metabolic parameters. Studies indicate significant benefits in insulin sensitivity and lipid profiles, with some variations across different IF protocols. Physiological insights reveal that IF leads to a metabolic switch from glucose-based to ketone-based energy, which plays a critical role in its effectiveness. Conclusions: Intermittent fasting appears to be a viable alternative to continuous calorie restriction for weight loss and metabolic enhancement. It not only aids in weight management but also offers additional health benefits such as improved insulin sensitivity and better lipid profiles. However, more long-term studies are needed to fully understand its benefits and potential risks. Future research should focus on optimizing fasting protocols and exploring their long-term effects on health and disease.